Meningkatkan Motivasi Belajar Siswa dengan Metode Problem Based Learning (PBL) Berbantuan Media Gambar Fase E Kelas X SMA Negeri 2 Sungai Raya Kabupaten Kubu Raya - Margaretha Yuli; Nerita Seetiyaningtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education in Indonesia aims to create a learning environment that supports the development of students' potential, including spiritual, intellectual, moral, and skills aspects. Although education has an important role in human resource development. In response to this challenge, the Independent Curriculum was introduced to restore learning affected by the pandemic, providing flexibility to educational units in adjusting the curriculum according to student needs. However, the achievement of learning achievement in Catholic Religious Education (PAK) at SMA Negeri 2 Sungai Raya is still less than optimal, mainly due to monotonous learning methods. This study proposes the Problem Based Learning (PBL) method as an alternative to improve student motivation and achievement. This study involved 9 students of class X FASE E, data was obtained through observation of activities and final tests for each cycle. This study aims to determine whether PBL assisted by image media can improve student learning motivation and how effective its application is in learning. The results are expected to show that students are more motivated and understand PAK material better. This is in accordance with the demands of 21st century learning which requires critical thinking skills, creativity, collaboration, and good communication.